Gastro-intestinal helminths in the red-bellied squirrel introduced in Argentina: accidental acquisitions and lack of specific parasites - Gozzi, Ana Cecilia (2014)
Introduced species may lose their natural parasites when invading a new habitat, may acquire new, local parasites or may introduce parasites from their native range. We studied the gastro-intestinal helminth fauna associated with the red-bellied squirrel Callosciurus erythraeus (Pallas, 1778) introduced in Argentina to evaluate its role as a host of either specific or acquired parasites in two invasion foci. We analyzed entire digestive tracts of 72 red-bellied squirrels captured in the main invasion focus (Luján, province of Buenos Aires) between February and May 2011, and in a secondary focus (Cañada de Gómez, province of Santa Fe) in December 2008. We only found two nematode specimens: an adult male belonging to the genus Pterygodermatites (Paucipectines) Quentin, 1969 and another adult male belonging to the genus Stilestrongylus (Freitas, Lent and Almeida, 1973). None of these genera were previously listed for the red-bellied squirrel in introduced areas, but a species of the genus Pterygodermatites was previously reported for this squirrel in its native habitat. These results indicate that, to date, the red-bellied squirrel in Argentina is accidentally parasitised by nematodes acquired in its new environment and has no specific gastro-intestinal helminths. This could be related with a “founder effect” and/or the lack of sciurid rodents that prevent the red-bellied squirrel to be colonized by pre-adapted helminth taxa. Other factors that may play a role are the small number of mammals with arboreal habits and some “encounter barriers” in the new environment that prevent the acquisition of helminths with a wide host spectrum.